Implementasi Penilaian Autentik di Madrasah Ibtidaiyah Hulu Sungai Selatan - Fitriah Fitriah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The existence of curriculum development from 2006 to the 2013 curriculum requires teachers to apply various aspects of curriculum development. One of them is changing the assessment system for student learning outcomes. The assessment used in the 2013 curriculum is authentic assessment, namely an assessment that is carried out in a comprehensive manner to assess all processes involved in learning, starting from input, process, and learning output. Based on this description, this study intends to dig deeper into the implementation of authentic assessment using descriptive qualitative research methods at two public elementary schools located in Kandangan Hulu Sungai Selatan District. The subjects in this study were authentic assessment problems, and the objects of this research were 4 classroom teachers, 1 teacher of the Aqidah Akhlak Subject, and 2 teachers of the Al-Qur'an Hadith Subject. As well as data collection in this study using interview techniques, observation, and documentation to clearly describe the research subject. The results of this study indicate that authentic assessment has been carried out in the two madrasahs, although they still face several obstacles, such as the many aspects that must be assessed with a large enough number of students, and the teacher is still in the adjustment stage. Keywords: Implementation, Authentic Assessment